[OA152] Output factor measurement in high-dose-per-pulse electron beams. (August 2018) - Pimpinella, Maria; Angelis, Cinzia De; Menegotti, Loris; Monaca, Sara Della; D'Arienzo, Marco; Andreoli, Stefano
Abstract : Purpose: The high dose per pulse of electron beams produced by some mobile accelerators for intraoperative radiotherapy can affect output factor (OF) measurements, since the dose rate increases by a factor larger than two from the reference to the smallest radiation field. Aim of this work was to assess the capability of different types of detectors to measure OFs at high dose per pulse by comparison with alanine dosimeters, which are independent of dose rate. Methods: Measurements were made in 9 and 7 MeV electron beams produced by a Novac 7 accelerator. PMMA cylindrical applicators with diameter of 100 mm (reference field), 70 mm, 60 mm, 50 mm and 40 mm were used. The dose per pulse varied from about 30 mGy, for the 100 mm applicator, to about 70 mGy, for the 40 mm applicator. OFs were determined using four types of plane-parallel ionization chambers (PTW Advanced Markus and Roos, IBA PPC40 and PPC05), two types of silicon diodes (PTW 60017 and IBA 3FG-3D), a PTW microDiamond and alanine dosimeters. Ionization chamber signals were corrected for ion recombination effects using a modified two-voltage-analysis method that includes the free-electron component. Results: A fairly good agreement was found between OFs measured by the three types of solid-state detectors and those measured by alanine. Differences were generally below 1% and maximum discrepancies around 2%. For the Advanced Markus and the PPC05 chambers differences from alanine results were below 1.7%. For the Roos and the PPC40 chambers agreement with alanine was within 2.3% down to the 50 mm applicator, while differences of several percent were found for the smallest applicator, most likely due to volume averaging effect. The variation of ion recombination correction factor with field size was below 1% for the Advanced Markus and the PPC05 chambers and up to about 10% for the Roos and the PPC40 chambers. Conclusions: Comparison with alanine measurements demonstrated that all the detectors considered in this work can be used to measure OFs in high-dose-per-pulse electron beams with an accuracy of 2%, provided that appropriate corrections for ion recombination effects are applied when using ionization chambers.